2014
DOI: 10.1007/s12272-014-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary in vitro and ex vivo evaluation of afzelin, kaempferitrin and pterogynoside action over free radicals and reactive oxygen species

Abstract: Biological activities of flavonoids have been extensively reviewed in literature. The biochemical profile of afzelin, kaempferitrin, and pterogynoside acting on reactive oxygen species was investigated in this paper. The flavonoids were able to act as scavengers of the superoxide anion, hypochlorous acid and taurine chloramine. Although flavonoids are naturally occurring substances in plants which antioxidant activities have been widely advertised as beneficial, afzelin, kaempferitrin, and pterogynoside were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Thus, the present paper reports the first suggestion of biological activity for this compound. Ellagic acid, kaempferol 3,7-di-O-rhamnoside (kaempferitrin), apigenin-6-C-glucoside (isovitexin) were reported with antioxidant and/or anti-inflammatory activities by several studies [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present paper reports the first suggestion of biological activity for this compound. Ellagic acid, kaempferol 3,7-di-O-rhamnoside (kaempferitrin), apigenin-6-C-glucoside (isovitexin) were reported with antioxidant and/or anti-inflammatory activities by several studies [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferitrin (Figure a) is a natural flavonoid glycoside that has been found in several edible and medicinal plants (Hamzah, Lajis, & Sargent, ). Kaempferitrin has been reported to possess broad bioactivities, such as antioxidative (Vellosa et al, ), anti‐inflammatory (De Melo et al, ), anticonvulsant (Gonzalez‐Trujano et al, ), antidepressant (Cassani, Dorantes‐Barron, Novales, Real, & Estrada‐Reyes, ), antidiabetic (Da Silva et al, ), and antitumor activities (Alonso‐Castro et al, ). It has been demonstrated that flavonoids have a protective effect against RA, which in part own to its anti‐inflammatory activity (Bala, Chetia, Dolai, Khandelwal, & Haldar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds isolated from flowers showed myeloperoxidase inhibitory (MPO) and radical scavenging activities 25 . Studies with flavonoids from this plant have demonstrated their antiproliferative effect against melanoma cells 26 , inhibition of MPO 27 , 28 , radical scavenging properties and antioxidant activities 29 32 , as well as a potent antifungal activity against opportunistic fungi 33 .…”
Section: Introductionmentioning
confidence: 99%